GARAP LAGU BAJU HÉJO: DAMPAK ADAPTASI SALENDRO 15 NADA PADA ANGKLUNG PENTATONIS RAGAM LARAS - Ega Fausta; Ananto Sabdo Aji (Keteg : Jurnal Pengetahuan, Pemikiran dan Kajian Tentang Bunyi, 2022)
Angklung Pentatonic Ragam Laras (APRL) is one of the innovative angklung products created in 2017 through an experimental process by Endah Irawan et al. A variety of tunings pentatonic angklung (APRL) is a musical ensemble consisting of several types of instruments made of bamboo material that apply the concept of collaborative instrumentation between gamelan orchestration and Western music. This ensemble is a new innovation in the world of traditional Sundanese art because it has a distinctive tuning pattern/scale system that collects several tuning patterns in Sundanese karawitan, namely Salendro, Degung and Madenda in different ensembles. The concept of the scale system is adapted from the concept of the Salendro 15 tone scale by R.M.A. Koesoemadinata.This study uses a mixed convergent parallel type method by obtaining both qualitative and quantitative data in order to answer the problem formulation comprehensively.  The research results show that the adoption of the 15-tones saléndro tuning by Koesoemadinata R.M.A. affects the musikal work on Baju Hejo song that have been re-arranged especially in terms    of the development of percussion and melodic patterns, tuning modulation and surupan, as well as the application of insert tones (miring and malang).